The Development of a Local Wisdom–Based Picture Storybook for Introducing Ogan Ilir Cultural Values to Early Childhood - Sarini Sarini; Sisca Cletus Lamatokan; Imamah Imamah (Kirana Publisher (KNPub), 2026)
The rapid development of globalization and information technology has influenced children's exposure to various cultures from around the world. While this condition provides opportunities for children to broaden their perspectives, it may also reduce their familiarity with local cultural values. Early childhood education plays an important role in introducing cultural identity and local wisdom from an early age. Therefore, learning media that integrate cultural values into children's learning activities are needed. This study aims to develop a picture storybook based on the local wisdom of Ogan Ilir as a learning medium to introduce cultural values to early childhood and to determine its feasibility and effectiveness. This research used a Research and Development (R&D) method with the ADDIE model which includes Analysis, Design, Development, Implementation, and Evaluation stages. The subjects of this study were 30 children aged 5–6 years in TK Pertiwi Indralaya, Ogan Ilir Regency. Data were collected through observation, interviews, expert validation questionnaires, and pre-test and post-test assessments. The results showed that the developed storybook obtained a feasibility score of 94% from material experts and 91% from media experts categorized as very feasible. The learning outcomes also showed improvement, with the average score increasing from 60.8 in the pre-test to 86.3 in the post-test.